Science in an Indigenous School: Insight into Teacher Beliefs about Science Inquiry and their Development as Science Teachers. Issue 1 (28th December 2015) - Rofe, Craig; Moeed, Azra; Anderson, Dayle; Bartholomew, Rex
Abstract : School science aspires for students to develop conceptual, procedural and nature of science understandings as well as developing scientific literacy. Issues and complexities surrounding the development of science curriculum for Indigenous schools in New Zealand is a concern as little is known about these aspects of science learning in wharekura (Māori Indigenous School). This paper draws upon the findings of an empirical study to address the call for research into effective practices for supporting Indigenous students in learning science. The study is part of a larger project investigating and extending our understanding about how New Zealand teachers' conceptualise science and science inquiry (investigation). Two Māori teachers participated in the research as well as their class who were supported by two researchers. Data were collected through in-depth interviews with teachers. This research reports the findings of how participating teachers' conceptualise science inquiry and describes their perceptions of how and why their students should learn science and science inquiry. The paper also presents teachers' views about their own development as science teachers and suggests two models to address the issue of science teaching in wharekura .